Clinical Efficacy and Meta-Analysis of Stem Cell Therapies for Patients with Brain Ischemia - Lukui Chen; Guilong Zhang; Ahsan Ali Khan; Xiaoyuan Guo; Yuchun Gu (Stem Cells International)
Objective. Systematic review and meta-analysis to observe the efficacy and safety of stem cell transplantation therapy in patients with brain ischemia. Methods. We searched Cochrane Library, PubMed, Ovid, CBM, CNKI, WanFang, and VIP Data from its inception to December 2015, to collect randomized controlled trials (RCT) of stem cell transplantation for the ischemic stroke. Two authors independently screened the literature according to the inclusion and exclusion criteria, extracted data, and assessed the risk of bias. Thereafter, meta-analysis was performed. Results. Sixteen studies and eighteen independent treatments were included in the current meta-analysis. The results based upon the pooled mean difference from baseline to follow-up points showed that the stem cell transplantation group was superior to the control group with statistical significance in the neurologic deficits score (NIHSS, MD = 1.57; 95% CI, 0.64–2.51; I2=57%; p=0.001), motor function (FMA, MD = 4.23; 95% CI, 3.08–5.38; I2=0%; p<0.00001), daily life ability (Barthel, MD = 8.37; 95% CI, 4.83–11.91; I2=63%; p<0.00001), and functional independence (FIM, MD = 8.89; 95% CI, 4.70–13.08; I2=79%; p<0.0001). Conclusions. It is suggested that the stem cell transplantation therapy for patients with brain ischemic stroke can significantly improve the neurological deficits and daily life quality, with no serious adverse events. However, higher quality and larger data studies are required for further investigation to support clinical application of stem cell transplantation.